1985
DOI: 10.1128/aem.49.4.874-878.1985
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and butanol inhibition of D-xylose and D-glucose uptake in Clostridium acetobutylicum

Abstract: Clostridium acetobutylicum exhibited diauxie growth in the presence of mixtures of glucose and xylose. Both glucose-and xylose-grown cells had a glucose uptake activity. On the other hand, growth on xylose was associated with the induction of a xylose permease activity, which was repressed by glucose in xylose-induced cells. The rate of sugar uptake with increasing sugar concentrations showed saturation kinetics with an apparent Km of 1.25 x 10-5 M for glucose and 5 x 10-3 M for xylose. Concomitant with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 15 publications
6
47
1
Order By: Relevance
“…The sucrose PTS was absent in both xylose and fructose grown cells, indicating that the system is inducible by its substrate. It remains possible that fructose may also repress the sucrose PTS (in fact we have preliminary evidence that this may indeed be the case), but it is very unlikely that the absence of sucrose PTS activity in xylose cells is a result of repression, as this is not a favoured substrate in this organism (Ounine et al 1985). Work in this laboratory has confirmed that mannitol and glucitol are also transported by inducible PTS transport mechanisms in Cl.…”
Section: Discussionmentioning
confidence: 67%
“…The sucrose PTS was absent in both xylose and fructose grown cells, indicating that the system is inducible by its substrate. It remains possible that fructose may also repress the sucrose PTS (in fact we have preliminary evidence that this may indeed be the case), but it is very unlikely that the absence of sucrose PTS activity in xylose cells is a result of repression, as this is not a favoured substrate in this organism (Ounine et al 1985). Work in this laboratory has confirmed that mannitol and glucitol are also transported by inducible PTS transport mechanisms in Cl.…”
Section: Discussionmentioning
confidence: 67%
“…However, in our assays using resting cells glucose did not inhibit xylose accumulation, and the mechanism by which glucose acts remains to be determined. A similar inhibition of xylose metabolism by glucose, involving repression of the xylose permease, has been observed in C. acetobutylicum [14] but the mechanisms responsible were not investigated.…”
Section: Discussionmentioning
confidence: 83%
“…The glucose PTS is constitutive, being found in cells grown on a variety of sugars, including fructose, galactose, maltose, sucrose, lactose, mannitol and glucitol (unpublished results). On the other hand, xylose transport in C. acetobutylicum is inducible [41], as are transport and metabolic activities for glucitol, mannitol and galactose (unpublished results). In C. thermocellum, glucose transport and metabolism was induced by glucose [27,50], while growth on fructose or mannitol led to induction of synthesis of a fructose PTS and fructose-l-P kinase, or a mannitol PTS and mannitol-l-P dehydrogenase, respectively [25].…”
Section: Induction Of Synthesis Of Catabolic Enzymes and Transport Symentioning
confidence: 91%
“…There are no examples of PTS-mediated pentose accumulation in bacteria, and thus pentoses are unlikely to be PTS substrates in clostridia. However, while xylose has been shown to be fermented by many clostridia, and in some cases transport has been assayed [41,42], there have been no detailed studies relating to the mechanism of uptake.…”
Section: Monosaccharides and Disaccharidesmentioning
confidence: 99%
See 1 more Smart Citation